Measuring Socio-Economic Resilience: The Role of Community-Based Tourism in Mitigating Income Disparities in Rural Areas - Latif; Rosandi Ardi Noegraha; Eva Purnamasari; Ita Erliyani; Muhammad Irfan Florid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Rural regions globally face persistent economic vulnerabilities, characterized by narrow economic bases, youth out-migration, and widening income disparities compared to urban centers. This study investigates the structural capacity of Community-Based Tourism (CBT) to foster socio-economic resilience and systematically mitigate income inequality in rural areas. Utilizing a mixed-methods approach, this research develops a comprehensive framework to measure resilience across institutional, economic, and social dimensions, while quantifying income distribution shifts using Gini coefficient adjustments and economic multiplier metrics. The findings demonstrate that structured CBT initiatives significantly redistribute economic returns by leveraging collective ownership and local supply chains, thereby reducing regional income disparities. However, the long-term sustainability of these mitigation effects depends heavily on local governance quality, equitable benefit-sharing mechanisms, and structural resistance to elite capture. This study concludes with actionable policy frameworks designed to optimize institutional support and scale CBT as a strategic instrument for inclusive regional development and rural economic stabilization.